2004
DOI: 10.1111/j.0736-8046.2004.21306.x
|View full text |Cite
|
Sign up to set email alerts
|

Periumbilical Allergic Contact Dermatitis: Blue Jeans or Belt Buckles?

Abstract: Nickel is the most ubiquitous contact allergen among children and adolescents. Metal blue jeans buttons and belts have been noted to cause nickel dermatitis around the umbilicus. For these children, traditional teaching is strict avoidance of all pants with metal snaps/buttons, particularly blue jeans. In this study we tested 90 pairs of blue jeans and 47 belts for nickel using the dimethylglyoxime spot test. Only 10% of blue jeans tested positive, while 53% of belts tested positive. Furthermore, 10 pairs of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Recently, it was demonstrated that 9 (10%) of 90 blue jeans and 25 (53%) of 47 belts from 6 local stores in Chapel Hill, NC, were positive on DMG testing. 31 The results from the current study make one speculate that excessive nickel release may also be identified in jewelry other than earrings in the United States. Furthermore, the accumulation of patch test data from the NACDG within the last 30 years revealed that the frequency of nickel sensitization increased significantly (P\.0001) from 11% in 1970 to 1972 to 16.9% in 2000 to 2002.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, it was demonstrated that 9 (10%) of 90 blue jeans and 25 (53%) of 47 belts from 6 local stores in Chapel Hill, NC, were positive on DMG testing. 31 The results from the current study make one speculate that excessive nickel release may also be identified in jewelry other than earrings in the United States. Furthermore, the accumulation of patch test data from the NACDG within the last 30 years revealed that the frequency of nickel sensitization increased significantly (P\.0001) from 11% in 1970 to 1972 to 16.9% in 2000 to 2002.…”
Section: Discussionmentioning
confidence: 64%
“…To illustrate the level of nickel exposure, 4 recent US surveys demonstrated excessive nickel release (as assessed by the nickel stick test) from a high proportion of earrings, clothing fasteners, buttons, and belt buckles. [35][36][37][38] Taken together, these results suggest that a regulatory intervention may be a useful tool when handling contact allergy epidemics.…”
Section: Discussionmentioning
confidence: 73%
“…Ni is one of the most potent allergens and an ubiquitous contact allergen among children and adolescents . The most frequent adverse reactions caused are hypersensitivity, subtoxic reactions, metal toxicity, and allergic contact dermatitis.…”
mentioning
confidence: 99%